REPRESENTASI PESAN MORAL DALAM FILM “THE THEORY OF EVERYTHING” (ANALISIS SEMIOTIKA ROLAND BARTHES) - Chafila Nursyifa Alifia (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2023)
ABSTRACT Film is not far from the word work of art, a film is not foreign to society by presenting entertainment, experiences, and new knowledge for the audience. The film directed by James Marsh entitled “The Theory Of Everything” is a genre film Biography, Drama, Romance which contains a lot of moral message to the first love story of Stephen Hawking’s life journey that led him to become a famous and successful physicist. The film is adapted from Jane’s 2007 book “Traveling to Infinity: My Life With Stephen”. The author aims (1) description of the meaning of Denotation in the film “The Theory Of Everything” by James Marsh (2) description of the meaning Connotation in the film “The Theory Of Everything” (3) Knowing myths in the film “The Theory Of Everything”. The theory used by the author is the theory of Roland Barthes using semiotic analysis consisting of Denotation, Connotation and Myth. The result obtained by the author are related to the representation of moral messages from Stephen Hawking in the film “The Theory Of Everything” the author finds a representation of Stephen Hawking’s life journey as a student majoring in Astrophysics by identifying the Denotation, Connotation and Myth in the scenes in the film “The Theory Of Everything” this research uses qualitative with Roland Barthes semiotic analysis approach. ABSTRAK Film tidak jauh dari kata karya seni, sebuah film bukan hal asing bagi masyarakat dengan menyajikan hiburan, pengalaman, dan pengetahuan baru bagi penonton. Film yang disutradarai oleh James Marsh berjudul “The Theory Of Everything” merupakan film bergenre Biography, Drama, Romance yang mengandung banyak tentang pesan moral hingga kisah cinta pertama dari Stephen dengan berbagai lika-liku perjalan hidup Stephen Hawking yang membawanya menjadi seorang fisikawan terkenal dan sukses. Film ini diadaptasi dari buku yang ditulis oleh Jane tahun 2007 lalu yang berjudul “Traveling to Infinity: My Life With Stephen”. Penulis bertujuan (1) deskripsi makna Denotasi dalam film “The Theory Of Everything” karya James Marsh (2) deskripsi makna Konotasi dalam film “The Theory Of Everything” (3) Mengetahui mitos dalam film “The Theory Of Everything”. Teori yang digunakan penulis adalah teori Roland Barthes dengan menggunakan analisis semiotika yang terdiri dari Denotasi, Konotasi dan Mitos. Hasil yang diperoleh penulis berkaitan dengan representasi pesan moral dari Stephen Hawking dalam film “The Theory Of Everything” penulis menemukan representasi perjalanan hidup Stephen Hawking sebagai mahasiswa jurusan Astrofisika dengan mengidentifikasi Denotasi, Konotasi dan Mitos yang ada dalam scene-scene dalam film “TheTheory Of Everything” penelitian ini menggunakan kualitatif dengan pendekatan analisis semiotika Roland Barthes.